Etiology and endoscopic profile of dysphagia in adults - Single center study at a tertiary care center in South India. - Sachin K. Dhande; Chandrasekar Murugesan; Anbalagan Pichaimuthu (International Journal of Medical Research and Review, 2022)
Background: Dysphagia is defined as difficulty in deglutition. It can be either structural or motility abnormality in the passage of food from the oral cavity to the stomach. Upper GI endoscopy is the most important tool to diagnose dysphagia and rule out premalignant and malignant lesions. The purpose of the study was to classify various causes of dysphagia. Methods: This prospective observational study was conducted on 206 patients with complaints of dysphagia. Detailed history, physical examination was done. Upper GI endoscopy was done in all cases, and biopsies were taken if required. Oropharyngeal and neurological dysphagia were excluded from the study. The statistical analysis was performed using Microsoft Excel. The mean, percentage and proportions were calculated. Results: Two hundred and six patients were included in the study. Out of 206 patients, 127 were females, and 79 were males. The mean age was 43.62 years. The commonest age group was 21- 40 years contributing 41.7% cases, followed by 41-60 years contributing to 30.8% cases. Benign etiology (n= 141) was more common than that of malignant (n= 65). The commonest benign etiology was reflux esophagitis (n =54) followed by esophageal candidiasis (n= 38). The commonest malignant etiology was adenocarcinoma of the esophagus (n= 38), followed by squamous cell carcinoma (n= 24). Conclusions: The upper GI endoscopy is effective and safe modality to diagnose dysphagia. Benign etiologies were more common among females, but malignant causes were more common among males. The incidence of esophageal malignancy increases with advanced age.